(untitled) (Economic and Political Thought, 2015)
In the present article, I verify the neo-functional assumptions about the development of European integration through successive crises. I advance a thesis that changes in the integration processes carried out during the crisis of the euro area are exceptional and they head in three directions. Firstly, it is typical of them to strengthen intergovernmentalism and political power of the largest Member States. Secondly, during the crisis, formal and informal competences of the EU technocratic institutions, including the European Commission and the ECB, increased. Both institutions yielded to the political pressure from powerful governments. This has led to a reduction in the autonomy of these institutions and their stronger subordination to the dominant Member States. Thirdly, the crisis has provided an opportunity to reinforce the segmentation of Europe into the eurozone and the “second circle of integration”.